The application prospect of microneedles for sports injuries: a narrative review - Ruihan Wang; Junqiu Wang; Tianyu Liu; Wei Wang; Shiqin Yin; Menglang Peng; Lei Zhang (Annals of Medicine)
Background The increasing participation in sports, driven by the popularity of physical activity and advancements in sports science, has led to a rise in sports injuries. Traditional treatments for sports injuries typically involve physical therapy and pharmacological interventions. However, drug therapy often suffers from low bioavailability, and analgesic and anti-inflammatory medications may also cause side effects such as gastrointestinal irritation and cardiovascular risks. To amplify the range of therapeutic options in the domain of sports injuries, microneedles (MNs) have emerged as a promising alternative.Methods A comprehensive review of English literature from the past two decades and more was performed across multiple databases, including PubMed, Embase, and Web of Science. The search utilized the keywords ‘microneedle,’ ‘sports injury,’ ‘drug delivery,’ etc. Original research articles, clinical studies, and reviews pertinent to the subject were included, while irrelevant and duplicate publications were excluded from the analysis.Results The diverse types and materials of MNs make them promising tools for treating sports injuries. These applications facilitate not only the targeted delivery of pharmaceuticals and biological materials but also enable continuous medical supervision through the assessment of subcutaneous metabolites.Conclusion The application of MNs in the management of sports injuries holds significant promise for therapeutic interventions and medical monitoring, offering valuable insights for future innovation in sports science applications.